A DC-link modulation scheme with phase-shifted current control for harmonic cancellations in multidrive applications - Yang, Y.; Davari, P.; Zare, Firuz; Blaabjerg, F. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2016)
© 2015 IEEE. This letter proposes a harmonic mitigation strategy to cancel out current harmonics induced by the front-end rectifiers in multidrive systems, which consist of diode rectifiers, silicon-controlled rectifiers (SCR), and boost converters in the dc-link. The proposed strategy is a combination of a new dc-link modulation scheme with a phase-shifted current control enabled by the SCR. The dc-link current modulation scheme is implemented by adding and subtracting specific modulation levels, which makes the total currents drawn from the grid "multilevel," resulting in an improved current quality. Simulations and experiments have validated the effectiveness of the proposed harmonic mitigation solution for multidrive systems.